Pengembangan Sumber Belajar Berbasis Budaya Lokal di Kelas IV SDN Sunju - Amiruddin, Ayu Cahyani; Herina, Herina; Firmansyah, Arif; Surahman, Surahman (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2025)
The purpose of this research is to develop a learning resource based on local culture in the 4th-grade class at SDN Sunju. This study uses development steps according to the Sugiyono model, which consists of 10 stages. Due to time and cost limitations, this research only follows 5 stages, which include: problem potential, data collection, product design, design validation, and design revision. 1) Problem potential, observations show that most of the teachers and students are from the Kaili ethnic group. Additionally, existing learning resources have not been optimally utilized to introduce and promote local culture. 2) Data collection, the researcher conducted field studies and literature reviews to gather information related to the learning resources being developed. 3) Product design, the researcher developed a learning resource based on the local culture of the area. 4) Design validation, after creating the culture-based learning resource, the researcher conducted a design validation involving three experts: a subject matter expert, a language expert, and a media expert. The results of the validation showed that the learning resource was valid and feasible for use, as seen from the average score of the subject matter expert 5 (very good), the language expert 3.96 (good), and the media expert 4.47 (very good). 5) Design revision, the researcher made revisions based on the advice and suggestions from the experts to improve the learning resource. From these results, it can be concluded that the culture-based learning resource is suitable for use in the learning process at school.